2011
DOI: 10.1161/strokeaha.110.596734
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acute Statin Therapy, Survival, and Improved Functional Outcome After Ischemic Stroke

Abstract: Background and Purpose-Statins improve infarct volume and neurological outcome in animal stroke models. We investigated the relationship between statin therapy and ischemic stroke outcome in the North Dublin Population Stroke Study. Methods-A population-based prospective cohort study was performed using rigorous ascertainment methods. Prestroke and acute (Յ72 hours) poststroke medications were recorded. Modified Rankin score and fatality were assessed at 7, 28, and 90 days and 1 year. Results-Of 448 ischemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 27 publications
2
81
0
Order By: Relevance
“…20 In addition, our data also agree with previous observations in nonthrombolysed patients which showed that statin continuation in the acute phase of stroke, compared with discontinuation of previous treatment or no statin use, was associated with improved outcome and decreased risk of short-term neurologic deterioration and long-term death. 6,9 A weakness of the present study is that there were some intergroup imbalances in variables known to be related to unfavorable outcome after IV rtPA. Specifically, stroke severity and prevalence of atrial fibrillation were both higher in the no statin group, while prior antihypertensive use and history of hypercholesterolemia were higher in the statin group.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…20 In addition, our data also agree with previous observations in nonthrombolysed patients which showed that statin continuation in the acute phase of stroke, compared with discontinuation of previous treatment or no statin use, was associated with improved outcome and decreased risk of short-term neurologic deterioration and long-term death. 6,9 A weakness of the present study is that there were some intergroup imbalances in variables known to be related to unfavorable outcome after IV rtPA. Specifically, stroke severity and prevalence of atrial fibrillation were both higher in the no statin group, while prior antihypertensive use and history of hypercholesterolemia were higher in the statin group.…”
mentioning
confidence: 80%
“…6 To date, very few studies have investigated the effect of statin use in the acute phase on ischemic stroke outcome. [7][8][9] The Stroke Prevention with Aggressive Reductions in Cholesterol Levels (SPARCL) trial showed a trend toward less severity for outcome 90 days after stroke with atorvastatin administration (80 mg), compared with placebo, in patients having a stroke during the trial. 10 So far, few studies have assessed the efficacy and safety of statin treatment in ischemic stroke patients treated with IV thrombolysis.…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that statins initiated before or immediately after ischemic stroke improved early and long-term survival and functional outcomes. 5 Second, higher serum total cholesterol and triglycerides are shown to be associated with better functional outcome and reduced long-term mortality after ischemic stroke, 3,4 but not with decreased risk for recurrent vascular events in the long term, which was the scope in our study. Third, our study included only patients with undetermined stroke etiology with no signs of smallvessel disease or any other probable or possible cause.…”
mentioning
confidence: 71%
“…A population-based prospective cohort study found that initiation of new statin therapy (< 72 hours after stroke) was associated with improved 7-day survival, along with good functional outcomes at 7 days and 1 year. 69 Statin use initiated within 3 days of stroke hospitalization is strongly associated with improved poststroke survival. By contrast, withdrawal of statin therapy in the hospital was associated with worsened survival.…”
Section: Neuroprotective Delivery Following Mechanical Thrombectomymentioning
confidence: 99%